Extending the RoboCup Rescue to Support Stigmergy: Experiments and Results - Jacobsen, Gabriel R. C.; Barth, Carlos A.; Santos, Fernando dos (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2012)
Social insects have inspired researches in computer sciences as well as engineers to develop models for coordination and cooperation in multiagent systems. One example of these models is the model of stigmergy. In this model agents use indirect communication (communication trough the environment) in order to coordinate actions. The RoboCup Rescue simulator is used as a testbed to evaluate this model in a real world considering a highly constrained scenario of an earthquake. This paper investigates the feasibility of using stigmergy in the RoboCup Rescue and the improvements of performance that the agents can be led to. We extended the RoboCup Rescue environment to enable the use of stigmergy by the agents in it. Experimental results shown that the use of stigmergy leads to an improvement on agents’ performance by 11.5% to 26%, depending on the scenario.